Comparative morphology on the egg chorion characters of some Noctuidae (Lepidoptera) - Dolinskaya, Irina V. (Zootaxa, 2016)
A comparative morphological analysis is provided for 70 species belonging to 59 genera of 13 subfamilies of Noctuidae from Ukraine. Diagnostic characters of the eggs for some species are identified. A comparison with representatives from other families of Noctuoidea is conducted. Some characters typical for separate species and general characters typical for most species are discussed.